Osteoporosis in Chronic obstructive Pulmonary Disease (COPD) Patients (Journal of Medicine, 2018)
Background: Osteoporosis is one of the most common systemic features of Chronic obstructive pulmonary disease (COPD). But there had been no data regarding osteoporosis in COPD patients in Bangladesh. Objectives: To determine the frequency of osteoporosis in COPD patients.Materials & Methods: This was a cross sectional observational study. COPD patients were recruited from Sarkari kormachari hospital. Patients were excluded if they had asthma, any disease affecting bones and calcium homeostasis or were receiving drugs related to bone metabolism. Demographic data were collected including age, smoking history, inhaled corticosteroid use, body mass index, treatment history hospital admission. Chest x-ray was done to exclude any infection or malignancy. Blood was obtained for complete blood count, renal function test, CRP. Bone mineral density (BMD; g/cm2) was conducted by using dual energy x-ray absorptiometry scan (DXA scan) at second to fourth lumbar spines (L2-4) and femoral neck.Results: The overall prevalence of osteoporosis according to the lowest T-score at either L2-4 or femoral neck were 56.7%. This is very high than other country. BMI and CRP were significantly associated with osteoporosis.Conclusion: The frequency of osteoporosis in Bangladeshi COPD patients was higher than others. Osteoporosis was associated with low BMI and high level of CRP.J MEDICINE JUL 2018; 19 (2) : 114-118